2007
DOI: 10.1007/s00428-007-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of follicular lymphoma by dual-color fluorescence in situ hybridization

Abstract: Follicular lymphoma (FL) is divided into two groups: one with the t(14;18)(q32;q21) and the other without this translocation but with other chromosomal abnormalities including t(3q27) break. The majority of FLs in Western countries have the former chromosomal changes with characteristic clinical features and low histological grades. The goal of this study was to investigate the characteristics of Korean FLs with regard to the underlying molecular defects. Sixty-one cases of FL were evaluated from two centers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The frequency in the majority of studies in Western countries (North America and Europe) is in the range of 80–100% . Data from the Asian countries are more scarce, and the range is approximately 50–80% . Our figure of 47% (42 of 90 cases) and that of 44% (25/57) from Korea are the lowest rates ever reported for FL .…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The frequency in the majority of studies in Western countries (North America and Europe) is in the range of 80–100% . Data from the Asian countries are more scarce, and the range is approximately 50–80% . Our figure of 47% (42 of 90 cases) and that of 44% (25/57) from Korea are the lowest rates ever reported for FL .…”
Section: Resultsmentioning
confidence: 54%
“…However, as there were only 13 cases in that report, this high rate may not be representative of the true incidence in Thailand. The Korean study showed the lowest rate (44%) of t(14;18) in FL, but this was biased because of a very high proportion (57%) of HG tumours . In that study, the t(14;18) rate among LG FLs was 70% (16/23 cases), which is similar to our finding of 63% (36/57), but both rates were significantly lower than that in the West.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Since the cases of grade 3 had the least translocations, it might be that they correspond to the 3B cases in Western countries [13]. …”
Section: Epidemiology Of Lymphomamentioning
confidence: 99%